1980
DOI: 10.1039/f29807601627
|View full text |Cite
|
Sign up to set email alerts
|

Viscosity dependent internal conversion in the rhodamine dye, fast acid violet 2R

Abstract: The fluorescence lifetimes of N-(2-tolyl)-N'-(2-tolyl-5-sulphon~te) rhodamine, Fast Acid Violet 2R, in a series of alcohols, range from 10 to 160 ps as a result of viscosity dependent ultrafast internal conversion. Rates of internal conversion are shown to be dependent upon the microviscosity, as opposed to the bulk viscosity of the solvent. Within a given homologous series of alcohols, the fluorescence lifetime (zf) was found to vary with solvent viscosity (q) according to a Forster-Hoffmann type equation: zf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
50
0

Year Published

1986
1986
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(56 citation statements)
references
References 0 publications
6
50
0
Order By: Relevance
“…[9] This value also gave a good fit for fluorescence lifetimes of Fast Acid Violet 2R, a rhodamine dye, in solutions of varying viscosity. [13] Importantly, the similar fluorescence lifetimes of the dye in monohydric and dihydric solvents with bulk viscosities differing by almost an order of magnitude showed that it is the microscopic rather than bulk viscosity which is the dominant factor in determining the decay rate. For perhaps the most widely studied molecular rotor, 9-(2,2-dicyanovinyl)julolidine (DCVJ) it was initially proposed that upon photoexcitation a twisted intramolecular charge transfer (TICT) state is formed, [14] with investigations to determine the nature of the intramolecular rotation and about which bond it occurs.…”
Section: Introductionmentioning
confidence: 97%
“…[9] This value also gave a good fit for fluorescence lifetimes of Fast Acid Violet 2R, a rhodamine dye, in solutions of varying viscosity. [13] Importantly, the similar fluorescence lifetimes of the dye in monohydric and dihydric solvents with bulk viscosities differing by almost an order of magnitude showed that it is the microscopic rather than bulk viscosity which is the dominant factor in determining the decay rate. For perhaps the most widely studied molecular rotor, 9-(2,2-dicyanovinyl)julolidine (DCVJ) it was initially proposed that upon photoexcitation a twisted intramolecular charge transfer (TICT) state is formed, [14] with investigations to determine the nature of the intramolecular rotation and about which bond it occurs.…”
Section: Introductionmentioning
confidence: 97%
“…as in diethylene glycol and glycerol. 24,25 A study of fluorescent life times and quantum yields was undertaken for two of our chromophores (MORPIP and AMINO) dissolved in a series of normal alcohols, diethylene glycol and glycerol to evaluate the influence of the viscosity and polarity of the medium on their luminescence properties.…”
mentioning
confidence: 99%
“…Previous studies indicate that this is due to the constraint placed on changes in molecular conformation during excitation by the hydrogen-bonding networks. 24,25 3.2 Glass forming solvents Solvents that form low temperature glasses have been extensively employed as matrices 17 for fluorophores. 43,44 If the increase in fluorescence quantum yield in viscous solvents is due to the constraining effect of the hydrogen bonding network a similar effect can be anticipated in glassy matrices.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Theoretical explanations of this phenomenon were given by Drexhage [28], who studied the dependence of the lifetime of RhB on the amino group's flexibility. Thus, upon excitation and due to the ability of rotation along the C-N bond, this probe displays a distortion in its excited state to form a twisted intra-molecular charge transfer (TICT) state [29][30][31]. This internal rotation results in a non-radiative decay; consequently, fewer lifetime values are exhibited [32].…”
Section: (D) Fourier Transform Infrared Spectroscopymentioning
confidence: 99%